Herbertia lahue (Iridaceae) and its allies - Deble, Leonardo Paz (Balduinia, 2022)
Herbertia lahue (Iridaceae) and its allies. Herbertia lahue is a taxon of difficult delimitation and the specific and infraspecific limits are reason of controversy among different authors. In this study, different populations of the species were analyzed along its range of occurrence in South America and also cultivated material from the state of Texas, United States. In order to complement the data, botanical collections deposited in different Herbaria and mentioned in Material and Methods were examined. Herbertia lahue, H. amoena and H. caerulea are considered segregated species. Lectotypes are designated for Herbertia amoena, H. caerulea and H. lineata. Herbertia furcata and Ferraria plana are considered doubtful taxa. Key Words: bibi, lahue, lahui, prairie-nymph, Herbertia amoena, Herbertia caerulea, Tigridieae.